2018
DOI: 10.1136/bmjopen-2017-016367
|View full text |Cite
|
Sign up to set email alerts
|

Nursing workload, patient safety incidents and mortality: an observational study from Finland

Abstract: ObjectiveTo investigate whether the daily workload per nurse (Oulu Patient Classification (OPCq)/nurse) as measured by the RAFAELA system correlates with different types of patient safety incidents and with patient mortality, and to compare the results with regressions based on the standard patients/nurse measure.SettingWe obtained data from 36 units from four Finnish hospitals. One was a tertiary acute care hospital, and the three others were secondary acute care hospitals.ParticipantsPatients’ nursing intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 29 publications
(30 reference statements)
2
78
0
18
Order By: Relevance
“…When investigating nurses’ daily workload using the RAFAELA system ( 10 ) , there was a greater chance of incidents (10% to 30%) and patient mortality (40%) when the values are above the ideal level and, conversely, this probability reduces 25%. It is inferred, therefore, that by assuming less workload, the nurse will have more time for care, preventing preventable clinical deterioration and patient incidents ( 10 ) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When investigating nurses’ daily workload using the RAFAELA system ( 10 ) , there was a greater chance of incidents (10% to 30%) and patient mortality (40%) when the values are above the ideal level and, conversely, this probability reduces 25%. It is inferred, therefore, that by assuming less workload, the nurse will have more time for care, preventing preventable clinical deterioration and patient incidents ( 10 ) .…”
Section: Introductionmentioning
confidence: 99%
“…It is inferred, therefore, that by assuming less workload, the nurse will have more time for care, preventing preventable clinical deterioration and patient incidents ( 10 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explain the magnitude of this situation, a metanalysis of 87 studies explored the relationship between nursing human resources dimensioning and in-hospital mortality. This study found a reduction of 2% to 7% in the mortality rates in the institutions in which there was adequate dimensioning of the nursing team (12) . Another study, conducted in South Korea, corroborates the above-mentioned finding, upon concluding that an unsafe care has a direct relation with a reduced number of nurses (13) .…”
Section: Discussionmentioning
confidence: 58%
“…These results were contradicted by [25,26] , whose results indicated that there is no significant changes in patient safety associated with decreased nursing work load. Also these results assert a trusting relationship between employees and management (interpersonal factors) supports a healthy work environment enhancing staff retention and effective patient care (patient care dimension) not infection control dimensions.…”
Section: Discussionmentioning
confidence: 90%